Insights into early molluscan neuronal development through studies of transmitter phenotypes in embryonic pond snails - Croll, Roger P. (Microscopy research and technique, 2000)
Pond snails have long been the subject of intense scrutiny by researchers interested in general principles of development and also cellular and molecular neurobiology. Recent work has exploited both these fields of study by examining the ontogeny of the nervous system in these animals. Much of this work has focussed upon the development of specific transmitter phenotypes to provide vignettes of neuronal subpopulations that can be traced from early embryonic life through to adulthood. While such studies have generally confirmed previous explanations of gangliogenesis in gastropods, they have also indicated the presence of several neurons that appear earlier and in positions inconsistent with classical views of gastropods neurogenesis. The earliest of these cells contain FMRFamide‐related peptides and have anteriorly projections that mark the future locations of ganglia and interconnecting pathways that will comprise the postembryonic central nervous system. These posterior, peptidergic cells, as well as certain, apical, monoaminergic neurons, disappear and apparently die near the end of embryonic life. Finally, populations of what appear to be peripheral sensory neurons begin to express catecholamines by around midway through embryonic life. Like several of the neurons expressing a variety of transmitters in the developing central ganglia, the catecholaminergic peripheral cells persist into postembryonic life. Transmitter phenotypes, cell shapes and locations, and neuritic morphologies all suggest that many of the neurons observed in early embryonic pond snails have recognizable homologues across the molluscs. Such observations have profoundly altered our views of neurogenesis in gastropods over the last few years. They also suggest the promise for pond snails as fruitful models for studying the roles and mechanisms for pioneering fibres, cues triggering apoptosis, and contrasting origins and mechanisms employed for generating central vs. peripheral neurons within a single organism. Microsc. Res. Tech. 49:570–578, 2000. © 2000 Wiley‐Liss, Inc.